RELIGIOUS PRACTICE AND CULTURAL PRESERVATION AMONG MUSLIM DIASPORA COMMUNITIES: CASE STUDY FOREIGN IKATAN KELUARGA PONDOK (IKPM) GONTOR - Nurcahyani, Ratna Alfina; Rabbani, Rifdah Syifa; Nursalsabila, Arifah; Susilowati, Ida (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
There are numerous challenges that Indonesian diaspora Muslims face, particularly in Europe, ranging from religious differences to inter-individual interactions influenced by liberal and secular values that might distort Islamic values. Muslims in the diaspora require a place in order to perform ibadah and preach with greater ease and safety. In response to these issues, Gontor established a group known as Ikatan Keluarga Pondok Modern, or IKPM, where Muslim diaspora actors can perform not only in their home country but also abroad. The purpose of this paper is to examine IKPM Gontor as a Muslim diaspora organization globally, particularly those in Russia, the United Kingdom, and Turkey, which have become well-known as effective teaching methods, and to examine the impact of IKPM Gontor’s education. The research method used is a qualitative research method using an integration and acculturation approach to diaspora studies.